Performance of a rotating impact-driven sprinkler with tapered and ring nozzle - Scaloppi, Edmar José; Colombo, Alberto; Gil, Ofelia de Fatima (Pesquisa Agropecuaria Brasileira, 2014)
The main objective of the present work was to evaluate the performance of two types of sprinkler nozzles, converging taper nozzle and ring nozzle, having the same inside diameter, under same pressure and different wind conditions. The parameters analysed were water distribution profile, distance of throw, water depths caught, and water distribution uniformity. The results obtained have shown that flow rate and distance of throw decreased substantially when ring nozzle was used, compared to the tapered one. Water distribution uniformity for ring nozzle was usually lower than that attained for tapered nozzle. These differences were much more critical under windy conditions and wider sprinkler spacings.
Keywords: sprinkle irrigation; sprinkler nozzles; water distribution; uniformity